PENGELOLAAN ZAKAT PERSPEKTIF HUKUM ISLAM KONTEMPORER - Abdain Abdain (MUAMALAH, 2015)
Islam provides guidance to its adherents who face problems of social inequality by placing charity as one of the main pillars of the Islamic establishment, especially in anticipation of the dynamics of growth and economic equality in society. As a source of funds, zakat potential to be used as capital for the development of Muslims, and will be very effective in anticipating the social gap in the middle of society. Classical scholars generally categorize that the taxable property zakat are: cattle, gold and silver, merchandise, treasure excavation and the latter is the result of agriculture. But in contemporary ijtihad today one represented by Yusuf Qardawi book, he breaks down a lot of models of wealth are subject to zakat, as many models and forms of wealth that was born from the more complex the economic activities. Yusuf Qardawi split into nine categories of zakat category; Farm animal charity, zakat of gold and silver which also includes money trade wealth zakat, zakat agricultural output includes land agricultural, honey and animal production zakat, alms minerals and marine products, zakat investment in plant, buildings and others, zakat search, services and professions and zakat stocks and bonds